MODEL SINERGISTIK PENGEMBANGAN KUALITAS LAYANAN PENDIDIKAN DI PASCASARJANA UNIVERSITAS LANGLANGBUANA BERBASIS MODEL QUALITY FUNCTION DEPLOYMENT - Yofi Syarkani (Scientia Regendi, 2020)
A service is difficult to measure, count, store, test and prove to guarantee a quality. Because the service is formless, the company has difficulty evaluating the quality of its service because it cannot see whether the quality of service received by the customer is exactly what is expected by the customer. The Langlangbuana University (Unla) Postgraduate Program has four study programs, namely Masters in Law, Masters in Management, Masters in Government Science, and Masters in Informatics Engineering facing special competition in organizing strata 2. This study aims at the extent to which the services organized by Unla Postgraduate in increasing the number of students.